1996
DOI: 10.2307/2265777
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients in Senesced Leaves: Keys to the Search for Potential Resorption and Resorption Proficiency

Abstract: Analyses of nitrogen and phosphorus in the senesced leaves of 89 species of deciduous and evergreen woody perennials were used (1) to discover the limits of ultimate potential resorption (maximal withdrawal of nutrients from senescing leaves), (2) to determine a means by which resorption can be categorized as complete or incomplete, (3) to develop the concept of resorption proficiency (measured as the levels to which nutrients have been reduced in senesced leaves), (4) to compare resorption in evergreen vs. de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

74
1,139
21
35

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 949 publications
(1,319 citation statements)
references
References 25 publications
(41 reference statements)
74
1,139
21
35
Order By: Relevance
“…An increase in the availability of N for the plant, due to SNF, leads to a decrease in N-resorption proficiency (NRP), that is, there is an increase in the concentration of N in the senescent leaves (Killingbeck 1996;Killingbeck & Whitford 2001). The data from the present study agree with these observations, given that the N concentrations found in senescent leaves for species without SNF were much lower than those with SNF (Fig.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…An increase in the availability of N for the plant, due to SNF, leads to a decrease in N-resorption proficiency (NRP), that is, there is an increase in the concentration of N in the senescent leaves (Killingbeck 1996;Killingbeck & Whitford 2001). The data from the present study agree with these observations, given that the N concentrations found in senescent leaves for species without SNF were much lower than those with SNF (Fig.…”
Section: Resultssupporting
confidence: 87%
“…Resorption proficiency is considered a more stable indicator of the plant capacity to reuse nutrients than resorption efficiency (Killingbeck 1996). An increase in the availability of N for the plant, due to SNF, leads to a decrease in N-resorption proficiency (NRP), that is, there is an increase in the concentration of N in the senescent leaves (Killingbeck 1996;Killingbeck & Whitford 2001).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations